Book Review: G. THEOTOKIS. The Norman Campaigns in the Balkans, 1081-1108. Warfare in History. Woodbridge: Boydell, 2014, pp.262. ISBN: 9781843839217 - SIMPSON, Alicia Josephine (Byzantina Symmeikta, 2016)
Book Review:G.THEOTOKIS. The Norman Campaigns in the Balkans, 1081-1108. Warfare in History. Woodbridge: Boydell, 2014, pp.262. ISBN: 9781843839217